ANALISIS PENGARUH KECERDASAN EMOSIONAL (EQ) DAN KECERDASAN SPIRITUAL (SQ) PADA KINERJA KARYAWAN - CAHYO TRI WIBOWO (Jurnal Bisnis dan Manajemen (Journal of Business and Management), 2015)
The purpose of this study serve to identify the influence analysis emotional intelligence and spiritual intelligence on performance employees (study at the PT. Bank Negara Indonesia, (Persero), Tbk Daerah Khusus Ibukota Jakarta and Surakarta Operation). This study is a descriptive empirical study with a quantitative approach. The type of data used is primary data and secondary data. The population in this study is the teller PT. Bank Negara Indonesia, (Persero), Tbk Daerah Khusus Ibukota Jakarta and Surakarta operation number (n) 146 with  sensus technique. Instrument research using emotional intelligence questionnaires (EQ), spiritual intelligence questionnaires (SQ), and performane questionnaires. Data analysis includes validity test, reliability test, the classical assumption test, and test hypotheses with linear regression as a tool of analysis using SPSS 17 for windows. Based on the discussion of the results of this study be concluded that emotional intelligence and spiritual intelligence affect the performance of the employees of PT. Bank Negara Indonesia, (Persero), Tbk Daerah Khusus Ibukota Jakarta and Surakarta operation.